PALEOPHYTOLOGÍA KURTZIANA III. 8. LA FLORA DEL CRETÁCICO SUPERIOR DE CERRO GUIDO, CHILE (1-2) (Ameghiniana, 2013)
The author describes a new species from the Maestrichtian flora of Cerro Guido: Hymenopbyllum priscum sp. nov. and ascribes to Thyrsopteris antiqua Menend., the specimens described by kurtz in 1899 as Asplenium dicksonianum Heer.